Detailed Morphological Changes of Foveoschisis in Patient with X-Linked Retinoschisis Detected by SD-OCT and Adaptive Optics Fundus Camera - Keiichiro Akeo; Shuhei Kameya; Kiyoko Gocho; Daiki Kubota; Kunihiko Yamaki; Hiroshi Takahashi (Case Reports in Ophthalmological Medicine, 2015)
Purpose. To report the morphological and functional changes associated with a regression of foveoschisis in a patient with X-linked retinoschisis (XLRS). Methods. A 42-year-old man with XLRS underwent genetic analysis and detailed ophthalmic examinations. Functional assessments included best-corrected visual acuity (BCVA), full-field electroretinograms (ERGs), and multifocal ERGs (mfERGs). Morphological assessments included fundus photography, spectral-domain optical coherence tomography (SD-OCT), and adaptive optics (AO) fundus imaging. After the baseline clinical data were obtained, topical dorzolamide was applied to the patient. The patient was followed for 24 months. Results. A reported RS1 gene mutation was found (P203L) in the patient. At the baseline, his decimal BCVA was 0.15 in the right and 0.3 in the left eye. Fundus photographs showed bilateral spoke wheel-appearing maculopathy. SD-OCT confirmed the foveoschisis in the left eye. The AO images of the left eye showed spoke wheel retinal folds, and the folds were thinner than those in fundus photographs. During the follow-up period, the foveal thickness in the SD-OCT images and the number of retinal folds in the AO images were reduced. Conclusions. We have presented the detailed morphological changes of foveoschisis in a patient with XLRS detected by SD-OCT and AO fundus camera. However, the findings do not indicate whether the changes were influenced by topical dorzolamide or the natural history.